The effectiveness of promotional mix in creating public awareness toward the products of Cruise Tasik Putrajaya / Tuan Nur Azyyati Tuan Muhammad Kamal - Tuan Muhammad Kamal, Tuan Nur Azyyati (2009)
The purpose of this research is to know the effectiveness of promotional mix in creating public awareness toward the products of Cruise Tasik Putrajaya (CTP). The promotional mix consists of elements such as advertising, sales promotion, publicity and personal selling. Nowadays promotional mix has gained importance within the country to achieving the competitive advantage. Moreover promotional mix has been used not by the profit organization but also the non profit organization. The findings show that the CTP have encountered problem in their promotional mix strategies in order to attract the consumers. The study is to find the level of public awareness toward CTP product and services through promotional mix that their uses, to determine the most effective promotional mix can enhance public awareness and to determine the promotional mix used by CTP effective in creating public awareness. As to solve the problem, the researcher suggests some of suggestions for the company to enhancing their promotional mix strategies. A total of 50 of respondents have been asked by using questionnaire in order to gain information and feedback to the company. The questionnaire consists of questions about the effectiveness of promotional mix in creating public awareness toward the products of CTP.